Practical Spring LDAP : Enterprise Java LDAP Development Made Easy - Varanasi, Balaji (Apress Imprint: Apress, 2013)
Practical Spring LDAP is your guide to developing Java-based enterprise applications using the Spring LDAP Framework. This book explains the purpose and fundamental concepts of LDAP before giving a comprehensive tour of the latest version, Spring LDAP 1.3.2. It provides a detailed treatment of LDAP controls and the new features of Spring LDAP 1.3.2 such as Object Directory Mapping and LDIF parsing. LDAP has become the de-facto standard for storing and accessing information in enterprises. Despite its widespread adoption, developers often struggle when it comes to using this technology effectively. The traditional JNDI approach has proven to be painful and has resulted in complex, less modular applications. The Spring LDAP Framework provides an ideal alternative.